PENGARUH METODE DISKUSI TERHADAP HASIL BELAJAR BAHASA INDONESIA PADA SISWA KELAS 4 DI SDN 231 PALEMBANG - Dewi Retnosari; Bukman Lian; Liza Murniviyanty (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine whether or not there is an effect of the discussion method on Indonesian language learning outcomes in grade 4 students at SDN 231 Palembang. This research is a quantitative experimental study using two classes: a control class and an experimental class. The research method used is a true-experimental design with a posttest-only control design. Data analysis includes normality test, homogeneity test, and hypothesis testing. The data collection technique used was a test. Posttests were conducted in each class, namely class IV.B and class IV.C. The posttest was conducted to determine the final learning outcomes between students who received treatment in the form of the discussion method and those who did not receive such treatment and were taught using the lecture method. The control class had an average score of 73.32, while the experimental class had an average score of 85.68. The final result of this study shows that there is a significant effect on student learning outcomes between those who were taught using the discussion method and those who were not. Therefore, the discussion method has a significant influence on the learning outcomes of grade IV students at SDN 231 Palembang.